Direct Visualization of Grain Boundaries in 2D Monolayer WS2 via Induced Growth of CdS Nanoparticle Chains. Issue 2 (14th September 2018) - Lan, Changyong; Li, Dapan; Zhou, Ziyao; Yip, SenPo; Zhang, Heng; Shu, Lei; Wei, Renjie; Dong, Ruoting; Ho, Johnny C.
Abstract: To date, wafer‐scale synthesis of two‐dimensional (2D) materials are well achieved by chemical vapor deposition, but the obtained monolayers typically have multidomains with electrical and optoelectronic properties affected by grain boundaries and domain sizes. When these 2D materials are used as the growth templates, these boundaries would also provide unknown influences to the successive heterostructure formation for extended applications. Here, for the first time, direct visualization of grain boundaries in monolayer WS2 film can be realized by the growth of CdS nanoparticles. Specifically, CdS is found to first preferentially nucleate and form as nanoparticle chains along WS2 grain boundaries in a random manner, independent of the grain boundary characteristics. Due to electron scattering and type II band alignment at the WS2 –CdS heterojunction, WS2 reduces in its mobility while becoming enhanced in its electron concentration. Notably, the WS2 –CdS heterostructure also yields improved carrier separation and collection for the photodetection performance enhancement. All these results can facilitate the detailed evaluation of crystalline grains‐related information of 2D materials and provide thorough understanding on the effect of these overgrown CdS on underlying WS2 monolayers, being extremely important to further optimize and enable their functionalities for advanced device applications. Abstract : Grain boundaries in chemical vapor deposited monolayer WS2 induce the growth of CdS nanoparticle chains there, making the grain boundaries visible. This overgrowth of CdS nanoparticles at the WS2 grain boundaries then leads to the formation of a type II heterojunction, which can reduce the carrier mobility while enhancing the photodetection performance of WS2 .